2015
DOI: 10.3389/fimmu.2015.00098
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Inflammation and Atherogenesis

Abstract: Platelets contribute to processes beyond thrombus formation and may play a so far underestimated role as an immune cell in various circumstances. This review outlines immune functions of platelets in host defense, but also how they may contribute to mechanisms of infectious diseases. A particular emphasis is placed on the interaction of platelets with other immune cells. Furthermore, this article outlines the features of atherosclerosis as an inflammatory vascular disease highlighting the role of platelet cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
167
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 178 publications
(180 reference statements)
1
167
1
9
Order By: Relevance
“…Platelets are the first responders of vascular injury during the early stages of endothelial disruption, after plaque rupture, and the final manifestation of disease; all the while, promoting the inflammatory processes that progress atherosclerotic disease (Nording, Seizer, & Langer, 2015; Rondina, Weyrich, & Zimmerman, 2013). Low-dose aspirin regimens and other anti-platelet strategies have been employed for both the primary and secondary prevention of acute events of occlusive arterial disease (Patrono & Baigent, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are the first responders of vascular injury during the early stages of endothelial disruption, after plaque rupture, and the final manifestation of disease; all the while, promoting the inflammatory processes that progress atherosclerotic disease (Nording, Seizer, & Langer, 2015; Rondina, Weyrich, & Zimmerman, 2013). Low-dose aspirin regimens and other anti-platelet strategies have been employed for both the primary and secondary prevention of acute events of occlusive arterial disease (Patrono & Baigent, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The role of platelets has been implicated in the formation and progression of atherosclerosis (Nording, Seizer, & Langer, 2015). Moreover, platelets take the center stage in acute coronary syndromes (ACS) when they form a thrombus upon the ruptured atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that platelet activation is not just linked to beneficial effects in hemostasis. Dysregulation of the coagulation cascade can lead to an aberrant activation and, thus, aggregation of platelets that is mostly associated with cardiovascular pathogenesis (reviewed in detail elsewhere [6,7,8,9]). In addition to their well-understood and indispensable hemostatic role, platelets are receiving more and more interest as immune and inflammatory effector cells [10].…”
Section: Introductionmentioning
confidence: 99%